Micropropagation of Philodendron sp. (Probably P. corcovadense) - Blanco, Mónica (2004)
Protocols for in vitro growth and multiplication, as well as for greenhouse acclimatization of this plant, were developed. In vitro establishment was successfully achieved in a Murashigue and Skoog (MS)(1962) medium supplemented with 0.8 mg l-1 of N6-bencil- adenine (BA), 2 mg l-1 of 3-indol-acetic acid (IAA), 30 g l-1 of sucrose and 8 g l-1 of agar. For multiplication, the explants were cultured on MS medium supplemented with 160 mg l-1 of adenine sulfate, 170 mg l-1 of NaH2PO4.H2O and 53 combinations of BA, 6-furfurylaminopurine (KIN), N6-(∆2-isopentenyl) adenine (2-ip), IAA, and α-naphtalene acetic acid (NAA). The highest rate of shoot multiplication, 3 shoots every four weeks, was achieved on MS medium containing 160 mg l-1 of adenine sulfate, 170 mg l-1 of NaH2PO4.H2O, 7mgl-1 of BA, 3 mgl-1 of KIN. In vitro rooting occurred on a hormone- free medium. Plantlets were successfully accli- matized in the greenhouse.